Clear aligner therapy in the mixed dentition: Indications and practitioner perspectives - Lynch, Nicholas M.; Shroff, Bhavna; Carrico, Caroline K.; Sawicki, Vincent; Sabol, Morgan; Lindauer, Steven J. (American journal of orthodontics and dentofacial orthopedics, 2023)
This study evaluated current trends and perspectives among orthodontists regarding clear aligner therapy in the mixed dentition (CAMD), including insights into perceived indications, compliance, oral hygiene, and other factors. An original, 22-item survey was mailed to a randomized, nationally representative sample of practicing orthodontists (n = 800) and a specific, randomized subsample of high-aligner-prescribing orthodontists (n = 200). Questions assessed respondents’ demographic information, experience with clear aligner therapy, and perceived advantages and disadvantages of CAMD compared with fixed appliances (FAs). Responses were compared using McNemar’s chi-square and paired t tests to assess CAMD vs FAs. One thousand orthodontists were surveyed, and 181 (18.1%) responded over 12 weeks. CAMD use was less common than mixed dentition FAs, but most respondents predicted an increase in their future CAMD use (57.9%). Among respondents using CAMD, the number of patients with mixed dentition treated with clear aligners was significantly lower than the number of total patients with clear aligners (23.7% vs 43.8%; P <0.0001). Fewer respondents considered skeletal expansion, growth modification, sagittal correction, and habit cessation feasible indications for CAMD compared with FAs (P <0.0001). Perceived compliance was similar for CAMD and FAs (P = 0.5841), but perceived oral hygiene was significantly better with CAMD (P <0.0001). CAMD is an increasingly common treatment modality for children. Most surveyed orthodontists reported limited indications for CAMD compared with FAs but perceived noticeable benefits for oral hygiene with CAMD. •Mixed dentition clear aligners are used significantly less than fixed appliances (FAs).•Mixed dentition clear aligners have more limited indications than FAs.•Perceived compliance is similar for clear aligners and FAs.•Perceived oral hygiene is better with clear aligners than with FAs.•The future use of mixed dentition clear aligners is predicted to grow.